Pengaruh Dimensi Kualitas Pelayanan Terhadap Kepuasan Pelanggan (Studi Kasus Pada Agen Jne Purnawarman) - Elsa Novianti bas; Dwindy Meyta; Eki Dudi Darmawan (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to establish the effect of the quality service on customer satisfaction (study case at JNE Purnawarman) and it applied descriptive methods by the quantitative approach. The method required nonprobability with incidental sampling. From the results of the method using the Solvin formula, the number of samples was 98 respondents. Based on the results of this study, the quality service variable has a simultaneous effect on the customer satisfaction variable (Y) with a significant f 0.000 < 0.05. The quality of service affects customer satisfaction by 58.6% while the remaining 42.4% from other factors.